2020
DOI: 10.1177/1457496920920474
|View full text |Cite
|
Sign up to set email alerts
|

Standard versus mini-percutaneous nephrolithotomy for renal stones: a meta-analysis

Abstract: Objective: To compare the standard percutaneous nephrolithotomy and mini-percutaneous nephrolithotomy in order to determine the optimal tract size for patients with renal stones. Methods: A systematic search of Web of Science, EMBASE, Cochrane Library, and PubMed databases was conducted for articles published through 20 August 2019, reporting on a comparison of the standard percutaneous nephrolithotomy and mini-percutaneous nephrolithotomy using the Preferred Reporting Items for Systematic Reviews and Meta-Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
19
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
5
19
1
1
Order By: Relevance
“…This may facilitate improvements in stone-free rates as smaller fragments are formed which can irrigate out through the tract. Similar to our study, improved effectiveness of mPNL was seen in a study by Zhong W., et al [21] where the mPNL was associated with significantly better SFR (89.7 vs 68.0%, p=0.049) compared to sPNL and lower need for a secondary procedure(13.8 vs 28.0%, p=0.048); and in the meta-analysis by Deng J, et al [22], where the stone-free rate was 87.6% with sPNL and 87.8% with mPNL (p=0.57). In our experience, higher SFR of mPNL among all types of renal calculi were, compared with sPNL (96.4 versus 91.8%, p=0.002).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…This may facilitate improvements in stone-free rates as smaller fragments are formed which can irrigate out through the tract. Similar to our study, improved effectiveness of mPNL was seen in a study by Zhong W., et al [21] where the mPNL was associated with significantly better SFR (89.7 vs 68.0%, p=0.049) compared to sPNL and lower need for a secondary procedure(13.8 vs 28.0%, p=0.048); and in the meta-analysis by Deng J, et al [22], where the stone-free rate was 87.6% with sPNL and 87.8% with mPNL (p=0.57). In our experience, higher SFR of mPNL among all types of renal calculi were, compared with sPNL (96.4 versus 91.8%, p=0.002).…”
supporting
confidence: 90%
“…Despite the higher safety profile mPNL a number of authors have reported differences in stone-free rate (SFR) in favor of sPNL. These differences are most notable when comparing the results of treatment of staghorn and multiple renal calculi [11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of multiple RCTs and meta-analyses, the current major guidelines do not recommend mPNL due to a lack of high-quality evidence. [ 2 3 ] This study by Zeng et al . is the first well-conducted multi-center, open-labeled RCT comparing sPNL with mPNL.…”
Section: Commentsmentioning
confidence: 99%
“…Similar to this study, Deng et al . [ 3 ] and Jiao et al . [ 2 ] noted a similar SFR in the two groups in their meta-analyses.…”
Section: Commentsmentioning
confidence: 99%